2013
DOI: 10.1002/oby.20345
|View full text |Cite
|
Sign up to set email alerts
|

Presence and dynamics of leptin, GLP‐1, and PYY in human breast milk at early postpartum

Abstract: ObjectiveThe presence of appetite hormones, namely glucagon-like peptide-1 (GLP-1), peptide YY (PYY) and leptin in breast milk may be important in infant feeding regulation and infant growth. This study evaluated whether concentrations of GLP-1, PYY and leptin change across a single feeding (from fore- to hindmilk), and are associated with maternal and infant anthropometrics.Design and MethodsThirteen postpartum women (mean ± SD: 25.6 ± 4.5 y, 72.0 ± 11.9 kg) provided fore- and hindmilk samples 4-5 weeks after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
66
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(80 citation statements)
references
References 38 publications
12
66
0
2
Order By: Relevance
“…Increasing evidence indicates that maternal obesity or over-nutrition induced increased milk leptin levels and placental leptin expression, developed leptin resistance, and led to obesity phenotype in the adults (Mühlhäusler et al, 2003;Muhlhausler et al, 2007;Schueler et al, 2013). In this study, we found that the offspring from maternal high-protein diet exhibited high serum leptin concentration at weaning, but they did not show increased food intake and fat accumulation in adulthood.…”
Section: Malementioning
confidence: 56%
“…Increasing evidence indicates that maternal obesity or over-nutrition induced increased milk leptin levels and placental leptin expression, developed leptin resistance, and led to obesity phenotype in the adults (Mühlhäusler et al, 2003;Muhlhausler et al, 2007;Schueler et al, 2013). In this study, we found that the offspring from maternal high-protein diet exhibited high serum leptin concentration at weaning, but they did not show increased food intake and fat accumulation in adulthood.…”
Section: Malementioning
confidence: 56%
“…ELISA in skim HM detected similar leptin levels (from 0.30 ± 0.04 ng/mL at 1 month to 0.10 ± 0.02 ng/mL at 12 months, n = 72) in a study by Bronsky et al [50], (0.28 ± 0.38 ng/mL, n = 651) in a study by Weyermann et al [27], and (0.16 ± 0.04 ng/mL, n = 28) in a study by Miralles et al [26]. RIA in skim HM also detected close leptin levels: (0.18 ± 0.15 ng/mL, n = 23) in a study by Schuster et al [28] and (1.00 ± 0.80 ng/mL, n = 13) in a study by Schueler et al [51]. RIA results in whole HM (1.34 ± 0.14, n = 24) in a study by Bielicki et al [52] were also comparable to our whole HM leptin levels.…”
Section: Discussionmentioning
confidence: 81%
“…Leptin is also contributed by lactocytes [19,20]. Previous studies have identified a positive correlation between maternal body mass index (BMI) and both maternal serum [21,22] and skim HM leptin [21,22,23,24], despite differing methodologies in leptin measurement [25]. However, no consistent relationship between maternal adiposity and HM leptin concentrations has been shown across lactation, with Miralles et al (2006) reporting only moderate correlations between maternal BMI and HM leptin during the first 6 months of lactation ( R = 0.387; p < 0.01) [8], while Bronsky et al (2011) saw no consistent relationship over the first 12 months of lactation [11], despite utilizing a similar leptin measurement methodology.…”
Section: Introductionmentioning
confidence: 99%
“…BMI is a poor measure of adiposity, as it fails to adequately differentiate between adipose tissue and lean body mass [26,27]. Investigations between the relationship of maternal BMI and leptin have been conducted predominantly in skim HM, which excludes the fat and cellular components of HM [21,24]. Further, leptin concentrations have been shown to be higher in whole HM compared to skim HM [20,23,28].…”
Section: Introductionmentioning
confidence: 99%